Annotated checklist of the tree flora of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2016)
Not available.This book is authored by Shukla Rani Basak and M. Khairul Alam.Bangladesh J. Plant Taxon. 23(2): 261-262, 2016 (December)